INVESTIGATING THE GENETIC DIVERSITY AND BIOTECHNOLOGICAL POTENTIAL OF ENDOPHYTIC FUNGI IN NIGERIAN MANGROVE ECOSYSTEMS FOR NOVEL BIOACTIVE COMPOUND DISCOVERY (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
The mangrove ecosystems in Nigeria, especially the Niger Delta and the Lagos lagoon, are biodiverse ecosystems that harbor endophytic fungi that have untapped potential of producing new bioactive compounds. The proposed research will also seek to explore the genetic variation and biotechnological uses of these fungi and how they can be used to solve antimicrobial resistance and other health problems in Nigeria. Sampling will focus on Bonny Island, Niger Delta, which is severely affected by oil pollution, and Ikorodu, which is mildly affected by anthropogenic activities, in the Lagos Lagoon to allow making comparative studies. The seasonal sampling of leaves, stems, and roots of dominant mangrove species will be done such as Rhizophora racemosa and Avicennia germinans. Isolation of endophytic fungi will be done through surface sterilization and culture on potato dextrose agar, morphological and molecular identification done using ITS rDNA sequences and genetic diversity evaluated with phylogenetic programs such as MEGA software. Fermentation, secondary metabolite extraction, pathogen assays (Staphylococcus aureus, Escherichia coli) and HeLa cancer cell assays will be used in bioactive screening, and compound identification will be done using the gas chromatography-mass spectrometry technique. The impacts of pollution will be evaluated by environmental parameters such as the pH in soil and the content of hydrocarbons. The demographic backgrounds are Donny Island with its population of around 309,200 (mainly Ibani Ijaw) who depend on fishing and oil supply and Ikorodu with its population of about 1,197,000 inhabitants in 2025 with different ethnic groups and involved in commerce and farming. The methods of primary data collection, which are field surveys and laboratory experiments, will expect at least 50 isolates, high genetic polymorphism, as well as correlations between stressors and metabolite production. This study will fill gaps in African mangrove microbiology, which will aid in discovering drugs in a sustainable manner and protecting the ecosystem.